A prospective study on the use of rivastigmine transdermal patch in Alzheimer’s dementia in a routine clinical setting - Nazir, Ejaz (Dement Neuropsychol, 2010)
There is not much published literature on the use of rivastigmine patch in a “routine” clinical setting. OBJECTIVES: In this naturalistic longitudinal observational study we sought to evaluate the safety, tolerability and efficacy of the rivastigmine patch in patients with early and late onset moderate Alzheimer’s disease in a routine clinical setting. METHODS: Out of all routine clinical referrals, the first 30 patients with diagnosis of moderate Alzheimer’s dementia who were started on rivastigmine patch were included in the study. Rivastigmine patch dose was titrated from 4.6 to 9.5mg/24 hours as appropriate. The primary outcome measure was safety and tolerability, measured by the incidence of adverse events and discontinuation due to any reason. The secondary outcome measure was to examine improvement on global, functional and behavioral domains as demonstrated by the MMSE (Mini Mental State Examination) score, BADLS (Bristol Activities of Daily Living Skills) score, patient and carer feedback and clinical judgment. RESULTS: Adverse events were reported in 20% of patients and 10% of total patients needed discontinuation of treatment. Improvement on global, functional and behavioral domains was observed in two thirds of patients whereas one third showed a relative decline. The most common side effect was skin irritation or erythema. CONCLUSIONS: The rivastigmine transdermal patch may provide a treatment option for those patients who require a change in their current oral cholinesterase inhibitor therapy due to safety or tolerability concerns.